(untitled) (Research, Society and Development, 2020)
Analyze the scientific evidence about the nurse’s duties in the screening of cervical cancer in patients seen at the Basic Health Unit. The study deals with a bibliographic review of the integrative literature review method, carried out in October 2020. The search carried out through the Virtual Health Library Platform - VHL, using the databases LILACS, BDENF, MEDLINE, IBECS, and through the Google Scholar Portal, adhering to the descriptors: “Nursing care”, “Patients "," Cervical cancer "," Basic Health Unit ", crossed with the operator by typing" AND ". It is necessary for nurses to have a holistic view, performing their work in a humanized and integral way. Thus, the control of cervical cancer is subject to actions aimed at health, cancer prevention and quality of life, so the nurse intervenes in these actions and others such as home visits and nursing consultation in a humanized and integrated way. Nursing has an essential role in the prevention of cervical cancer, identifying high-risk populations, developing actions for planning, controlling and supervising education and prevention programs, and thus contributing to an early diagnosis of the disease.